GENETIC GAIN AND PROJECTED INCREASE IN STAND VOLUME FROM TWO CYCLES BREEDING PROGRAM OF Acacia mangium - Arif Nirsatmanto; Teguh Setyaji; Sri Sunarti; Dwi Kartikaningtyas (Indonesian Journal of Forestry Research, 2016)
Two cycles breeding program of Acacia mangium was practiced by Center for Forest Biotechnology and Tree Improvement Research. Although improved seed from the breeding program have been used in operational plantation, the real amount of gains in productivity was not verified together yet.  This study was aimed to observe realized genetic gain and projected increase in stand volume from the two cycles breeding of A. mangium, and to discuss the implications on plantation productivity and sustainable forestry in Indonesia. Improved seed from first and second-generation seed orchard were tested together with an unimproved seed in genetic gain trial in West Java, with spacing of 3 x 3 m. Measurements were done at three years ages for height, dbh, and stem volume. Realized genetic gain was calculated as the percentage increase of improved seed over the unimproved one. Results of study showed that improved seed performed better growth than the unimproved with realized gain of 5-24% (height), 3-44% (dbh) and 11-90% (stem volume). Improved seed from second-generation outperformed that from the first-generation, with an improvement of 6-16% (height), 3-26% (dbh) and 20-53% (stem volume). Genetic gains increased with increasing ages for height, but it tended to decrease for dbh and stem volume. At given site and silvicultural practices, projected increase in stand volume at 8 years rotation reached 290-325 m3/ha, which is equal to 30-50% of gains. The uses of high genetically improved seed, in combination with intensive silviculture, would provide significant impacts on plantation productivity and sustainable forestry in Indonesia.